Reproductive performance of Black Bengal goat under semi-intensive and extensive condition in Rajshahi district of Bangladesh - Hasan, Md Jahid; Ahmed, Jalal Uddin; Alam, Md Mahmudul; Mojumder, Mohammad Liaquat Osman; Ali, Md Showkat (Asian Journal of Medical and Biological Research, 2015)
The present study was carried out to investigate the status of different reproductive parameters of Black Bengal in a rural area of Mukterpur under Charghat Upazilla of Rajshahi district during the period of July to December/2012. A total of 200 Black Bengal goats under both semi-intensive (n=100) and extensive condition (n=100) were selected on the basis of age, weight, body shape and conformation. The average age at puberty was 197.82±12.58 days and age at first conception was 292.96±0.50 days under semi-intensive condition whereas 208.82±12.60 days and 287.65±0.52 days under extensive condition. Age at first kidding was 448.26±25.48 days under semi-intensive condition whereas under extensive condition it was 450.07±22.43 days. Average litter size in the first, second and third parity was 1.06, 1.76 and 1.96, respectively under semi-intensive condition whereas under extensive condition, these were 1.01, 1.76 and 1.96, respectively. The average kidding interval of goats under semi-intensive and extensive conditions were 190.2±20 and 178.23±.50 days, respectively and the difference between these two was statistically significant (p<0.01). Sex ratio of male and female kids born was found to be 56 : 44, 44 : 56 and 55 : 45 in the first, second and third parity, respectively under semi-intensive condition whereas, it was 55 : 45, 48 : 52 and 54 : 56 in the first, second and third parity, respectively under extensive condition. The usual numbers of kids at one time in Black Bengal goats varied from single to quadruplet. Average post partum weight of does was higher under semi-intensive condition than extensive condition which was statistically significant (p<0.05). Age of kid mortality was more in first parity under one month of age but gradually decreased with the age of kids under both semi-intensive condition and extensive condition. The average birth weight of kids was 1.28 ± 0.11 kg and 1.25 ± 0.10 kg under semi-intensive and extensive condition respectively which was statistically significant (p<0.01). Average birth weight of male was higher than female under both conditions. Kid mortality increased from 2 to 21% with the increase of parity. Birth weight of kids was higher in July-October and kid mortality was higher in winter season. The age at puberty was found earlier in summer season than others seasons under both semi-intensive and extensive conditions. Reproductive performances of Black Bengal goat were better in third parity than that of the first and second parity under both conditions. Asian J. Med. Biol. Res. June 2015, 1(1): 22-30